A theoretical review of interpersonal emotion regulation in eating disorders: enhancing knowledge by bridging interpersonal and affective dysfunction - Kara A. Christensen; Ann F. Haynos (Journal of Eating Disorders, 2020)
Abstract Individuals with eating disorders (EDs) frequently report interpersonal and affective dysfunction. A useful lens for uniting these ideas is through the framework of interpersonal emotion regulation (IER), which consists of the ways others assist a distressed individual and how this shapes his or her subsequent emotional, behavioral, and cognitive responses. In this theoretical review, we provide an overview of the rationale for exploring IER and review IER processes in this population using the framework of the Process Model of Emotion Regulation. Finally, we offer suggestions for next steps in conducting research. IER offers a parsimonious way to explore social and emotional constructs related to ED pathology and may provide potential targets for prevention and intervention in these difficult-to-treat disorders.